Pemberdayaan Masyarakat Desa Danau Ganting Melalui Optimalisasi Wisata Alam Danau Ganting Barito Selatan - Mariadi, Mariadi; Ahmad, Sabarudin; Kumalasari, Mai Ratih; Lucia, Waredayani Anisa; Andriani, Lisa (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The purpose of this activity is to see the potential of Ganting Lake so that it can be used as a natural tourist destination. The Asset Based Community Development (ABCD) service method. The results obtained from this activity are that Lake Ganting has the potential to be developed as a natural tourist destination because its beauty is no longer in doubt. Furthermore, the interest of the local community and newcomers from outside to have recreation at Ganting Lake is very large , and the people in Danau Ganting Village welcome it if Lake Ganting can be used as a natural tourist destination so that the beauty of the lake can be exposed and many people can visit and indirectly improve the economy of the people in Danau Ganting Village. However, the role of the Barito district government The South must take part in realizing the natural tourism potential of Ganting Lake